If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 5)(5x + 1) = -19 Reorder the terms: (5 + x)(5x + 1) = -19 Reorder the terms: (5 + x)(1 + 5x) = -19 Multiply (5 + x) * (1 + 5x) (5(1 + 5x) + x(1 + 5x)) = -19 ((1 * 5 + 5x * 5) + x(1 + 5x)) = -19 ((5 + 25x) + x(1 + 5x)) = -19 (5 + 25x + (1 * x + 5x * x)) = -19 (5 + 25x + (1x + 5x2)) = -19 Combine like terms: 25x + 1x = 26x (5 + 26x + 5x2) = -19 Solving 5 + 26x + 5x2 = -19 Solving for variable 'x'. Reorder the terms: 5 + 19 + 26x + 5x2 = -19 + 19 Combine like terms: 5 + 19 = 24 24 + 26x + 5x2 = -19 + 19 Combine like terms: -19 + 19 = 0 24 + 26x + 5x2 = 0 Factor a trinomial. (4 + x)(6 + 5x) = 0Subproblem 1
Set the factor '(4 + x)' equal to zero and attempt to solve: Simplifying 4 + x = 0 Solving 4 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + x = 0 + -4 x = 0 + -4 Combine like terms: 0 + -4 = -4 x = -4 Simplifying x = -4Subproblem 2
Set the factor '(6 + 5x)' equal to zero and attempt to solve: Simplifying 6 + 5x = 0 Solving 6 + 5x = 0 Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 5x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + 5x = 0 + -6 5x = 0 + -6 Combine like terms: 0 + -6 = -6 5x = -6 Divide each side by '5'. x = -1.2 Simplifying x = -1.2Solution
x = {-4, -1.2}
| 5(x^2-12x)+4x(7-3x-2x^2)= | | 3y(5y^2-8)= | | 2x+3x+12=27 | | 8+6x-3x=29 | | y=240-.8x | | y=240-.8x | | -10=5v+2+7v | | -83=4(1+3r)-3 | | 4x/5=8 | | (x+4)(3x+2)=-7 | | 8x-9/3=13 | | x=210-.7y | | y=x^2-13+30 | | -125^(-2/3) | | 4v+4+v=-3 | | 5x-5-2x=4 | | (8x)/(x^4+8x^2+16) | | 5x(5x+2)=8 | | 2(5-x)=5(x-5) | | -5+x/3=0 | | C=r+(u-3)sforu | | C=r+(u-3)s | | 3x-4=5x+18 | | 2(5-x)=5(2x-6) | | 8x-8-3x=7 | | 4x+12+2x=12 | | -5r-7r=24 | | 155=-5(8b+1) | | 6x-3(0)=6 | | 2x^2/8-x | | 9=-2n-7n | | 6(0)-3y=6 |